Sleep deprivation in development of obesity, effects on appetite regulation, energy metabolism, and dietary choices - Akhlaghi, Masoumeh; Kohanmoo, Ali (Nutrition research reviews, 2025)
Sleep deprivation, which is a decrease in duration and quality of sleep, is a common problem in today's life. Epidemiological and interventional investigations have suggested a link between sleep deprivation and overweight/obesity. Sleep deprivation affects homeostatic and non-homoeostatic regulation of appetite, with the food reward system playing a dominant role. Factors such as sex and weight status affect this regulation; men and individuals with excess weight seem to be more sensitive to reward-driven and hedonistic regulation of food intake. Sleep deprivation may also affect weight through affecting physical activity and energy expenditure. In addition, sleep deprivation influences food selection and eating behaviours, which are mainly managed by the food reward system. Sleep-deprived individuals mostly crave for palatable energy-dense foods and have low desire for fruit and vegetables. Consumption of meals may not change but energy intake from snacks increases. The individuals have more desire for snacks with high sugar and saturated fat content. The relationship between sleep and the diet is mutual, implying that diet and eating behaviours also affect sleep duration and quality. Consuming healthy diets containing fruit and vegetables and food sources of protein and unsaturated fats and low quantities of saturated fat and sugar may be used as a diet strategy to improve sleep. Since the effects of sleep deficiency differ between animals and humans, only evidence from human subject studies has been included, controversies are discussed and the need for future investigations is highlighted.